PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PROVINSI LAMPUNG - Indriani Indriani; Masayu Nila Juwita (Universitas Bandar Lampung (UBL), 2022)
The performance of employees at the Population and Civil Registration Office of Lampung Province is generally still low, this can be seen from the number of employees who have low work discipline, come and go not in accordance with applicable office rules, there are employees in completing tasks that are not in accordance with the set targets, the lack of employee innovation in work and loyalty to work is still low, this results in some agency activity programs that are not achieved according to the set targets. The low performance of employees is indicated because the organizational culture in the Population and Civil Registration Office of Lampung Province such as a culture of honesty, a culture of perseverance towards work, and a culture of discipline has not been entrenched and seems to be only used as a slogan, superior culture provides opportunities for employees to take the initiative in carrying out tasks. is not yet entrenched, subordinates are rarely involved in making decisions, a culture of discipline, obeying the applicable office rules is less entrenched. In addition, employee work motivation is generally still low, this is indicated as completion of work that is often late, always waiting for orders to complete every routine work, lack of initiative and creativity in completing work.The purpose of this study was to analyze the influence of organizational culture and work motivation on employee performance at the Department of Population and Civil Registration of Lampung Province. This type of research is descriptive quantitative with a survey approach, with a population of 41 people. Data related to research variables were collected using questionnaires distributed to all respondents and filled out by respondents themselves based on respondents' perceptions. Techniques of data analysis using multiple linear regression. The results show that organizational culture has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance. Respondents dominantly considered that the organizational culture at the Population and Civil Registration Office of Lampung Province had run quite well, work motivation at the Lampung Province Population and Civil Registration Service had been running quite well and the performance of employees at the Lampung Province Population and Civil Registration Service had been going quite well.